Interdisciplinarity in the methodology of teaching in Health: A Literature Review. - Andrade , Aléxya Eduarda; Antunes , Amanda Café Ribeiro; Oliveira, Wyderlannya Aguiar Costa de; Diniz, Itamara Augusta; Dias, Leonardo dos Santos; Ribeiro, Joseana Moreira Assis; Silva, Maurício de Jesus; Oliveira, Fhelipe Aguiar Costa de; Silva, Geisa Cabral Carneiro da; Santos , Rafael Pereira dos; Azevedo, Samara Cristina Guimarães de; Flores, Ilana Freitas Freire de Carvalho Cairo; et al. (Brazilian Journal of Implantology and Health Sciences, 2023)
The objective of this article is to carry out a sweep of the current medical literature on the relationship between interdisciplinarity in the methodology of teaching in Health. keywords “Teaching, Health, Interdisciplinarity, Health Education”. Articles with more than 20 years of publication or that did not fit within the scope of the research were excluded. In all, 10 articles that fit within the search patterns were selected. It is concluded that most publications promote the need for changes in Health Education in higher education and in learning, knowledge and management of the SUS, in order to promote the Significant Learning of graduates in their professional careers.